2013
DOI: 10.1016/j.ygyno.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Loss of DOK2 induces carboplatin resistance in ovarian cancer via suppression of apoptosis

Abstract: We have developed a screening methodology that analyzes the epigenome and informatically identifies candidate genes followed by in vitro culture screening of the candidate genes. To validate our screening methodology we further characterized one candidate gene, DOK2, and showed that loss of DOK2 induces chemotherapy resistance by decreasing the level of apoptosis in response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 38 publications
7
56
0
Order By: Relevance
“…These results indicate that DNA methylation involves the regulation of multidrug resistance in ovarian cancer through apoptosis. The latter finding is in good agreement with that of previous studies (86,87). As shown in Table I, there are at least seven genes, including PTEN, BLU and UCHL1, that participate in the regulation of multidrug resistance in ovarian cancer through cell apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that DNA methylation involves the regulation of multidrug resistance in ovarian cancer through apoptosis. The latter finding is in good agreement with that of previous studies (86,87). As shown in Table I, there are at least seven genes, including PTEN, BLU and UCHL1, that participate in the regulation of multidrug resistance in ovarian cancer through cell apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…ErbB signaling (91), focal adhesion (92,93), apoptosis (94,95) and p53 signaling (96,97) have been reported to associate with drug resistance in ovarian cancer. For example, miR-21 regulates drug resistance via apoptosis and cellular survival pathways (94), and loss of DOK2 induces carboplatin resistance in ovarian cancer via suppression of apoptosis (98).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that the loss of DOK2 induces carboplatin resistance in ovarian cancer through the suppression of apoptosis [56]. Moreover, DOK2 was found to act as a potential tumor suppressor in human breast cancer [57].…”
Section: Inferring Putative Cancer Genesmentioning
confidence: 98%